IMPACT OF ADHD ON ADOLESCENCE BEHAVIOR AND OTHER COMORBIDITIES FOCUSED ON CONDUCT DISORDERS, ODD/CD AND ANXIETY DISORDER - Ekbote, Unnati (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The purpose of this research proposal is to conduct a study of ADHD impact on adolescence behavior and other comorbidities. ADHD is the neurological disorder which is the most common childhood disorders and characterized by a persistent and trans-situational pattern of age-inappropriate inattention, hyperactivity, and impulsivity. The aim of the research subject is to find out how it is impacting adolescence behavior and develop other comorbidities such as anxiety disorder, eating disorder, ODD/CD along with analyzing the impact, causes, relations and solutions addressing the same.